A Theoretical Model of Drug/DUI Courts: An Application of Structural Ritualization Theory - Bin Liang (American journal of criminal justice, 2016)
Past studies of Drug/DUI courts primarily focused on outcome evaluation and policy-driven issues, but lacked an effective theoretical framework for understanding drug court programs, in particular the interaction between the program and clients. In this study, we apply structural ritualization theory (SRT) to the Drug/DUI program and argue that such programs serve two key functions, to disrupt clients’ old rituals (e.g., drug/alcohol abuse, committing crimes), and to help lay a foundation for building new abstinent and noncriminal ritualized practices for clients both in and after the drug court program. We further argue that the effectiveness of drug program functions and services at the organizational level and the success of clients’ transformation at the individual level can be empirically measured and studied by four elements of SRT, including salience, repetitiveness, homologousness, and resources. Policy implications are drawn based on the contribution of SRT.